A flight of no substance, collapsing space in its wake. (1st June 2021) - Eeckhout, Riet
This article looks at ways in which architecture can be articulated as a sensation within the drawing. The subject of occupying drawings is considered here as a result of entering the drawing, an action John Hejduk describes 'as a flight of no substance', collapsing space between the observer and the artefact in its wake. entering the drawing and subsequently occupying the drawing is considered here as a phenomenon that enables experiential and observational proximity to an artefact and its embedded subject. The collapsing mechanism enforces thinking about the observational intent of this type of entering, its relationship with immediacy and with aspects of the non-representational. Furthermore, the act of entering the drawing is viewed as a technique for mediating and bringing forth subject matter in the drawing. This technique of augmented observation and mediation is in service of the quest for subject presence in the drawing, as opposed to subject representation in the drawing ‐ allowing a residence in close encounter by the maker during production and later by the observer of the resulting artefact. The article is accompanied by a set of drawings from the Drawing Out Gehry series. The drawings are driven by an interest in relational encounters and space they take in. Away from an object or component-directed perception of space and towards the understanding of space as the relationship between elements, this set of drawings is in search of the quality and intrigue raised by the architectural event as the encounter of spatial circumstances.